El juego de azar y el videojuego en la Universidad de San Buenaventura Medellín (2007)
This current study consists of the description of the use of games of chance and video games in the students, instructors and employees at Saint Bonaventure University, Medellin branch and their relation to the physical dimension with variables like the following: concentration difficulties, change in mood, physical problems, preference of games to sports, as well as the relaxation produced by the game; at this first moment, partial results in students are shown here. For this, it was given a questionnaire to a sample of 461 students of a total population of 2930 freshmen of 2006, for a 95% of validity and a margin of error of 5%. For the systematization and the statistical analysis, the Epi-info program was used. It is important to remark here that this study was backed by the Interdisciplinary Group of Psychosocial Studies in Addictions – GIEPSA, which belongs to the Center of Research and Attention to the Drug addict, - CIAF-, directed by Francisco Javier Arias Zapata